Cumhuriyet döneminde spor (1923 - 1938) - Tüfek, Sabri Sami (My University, 2019)
Türkiye Cumhuriyeti’nin kuruluşuna ve Atatürk’ün vefatına kadar geçen süreçte Türkiye’de spor alanında yapılan çalışmalar üzerinde durulmuştur

This study focuses on the activities which were carried out in the fields of sport during the periods of the National Struggle years, the establishment of the republic of Turkey till the Atatürk's death.
Keywords: CUMHURİYET; OLİMPİYAT; SPOR; Sport; Turkey Training Community Alliance; TÜRK SPOR KURUMU Republic